2018
DOI: 10.14419/ijet.v7i2.29.14294
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Knowledge Management and Usage of Medicinal Plants as Daily Medication in Healing Rituals Among the Batek of Kuala Koh, Gua Musang, Kelantan :an Exploratory Evidence

Abstract: Traditional knowledge related to medicinal plants of the indigenous people are indeed a useful asset for the community. The knowledge that had been traditionally inherited from their ancestors is an integral part of their survival as they live symbiotically with the forests. While many researches and literatures are focusing on documenting and recording these knowledge, not much has been researched in understanding the holistic process of the knowledge management particularly at the indigenous community level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In contrast, studies among Orang Asli living in deep forests and inland locations have reported the opposite situation. The Semai from the Senoi group 30 and the Batek from the Negrito group 31 are still primarily practising traditional lifestyles and medicine, especially in the healing of ailments.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies among Orang Asli living in deep forests and inland locations have reported the opposite situation. The Semai from the Senoi group 30 and the Batek from the Negrito group 31 are still primarily practising traditional lifestyles and medicine, especially in the healing of ailments.…”
Section: Discussionmentioning
confidence: 99%